Monitoring and assessment of drought in Shaqlawa district using (VHI – TCI) indicators - Rashid Haji Muhamad Saleem; Sarhad Hadi taha (QALAAI ZANIST JOURNAL, 2024)
Monitoring and assessing drought is an important issue for the current regions of the Kurdistan Region, especially after the past few years, most of the regions of the Kurdistan Region have experienced drought. This study attempts to use remote sensing (RS) and Geographic Information System (GIS) based on Landsat satellite imagery (4 - 8) for the month (April) of each year (2008-2015-2022). Drought in the study area (Shaqlawa district) is presented through different indicators of drought such as Temperature Condition Index (TCI), Vegetation Health Index (VHI), and using Land Surface Temperature (LST) for temperature conditions by applying them on satellite images through RS and GIS programs, we were able to achieve the objectives of the research.